The Materiality of the Archive Creative Practice in Context - Breakell, Sue; Russell, Wendy (Routledge Studies in Archives, 2024)
The Materiality of the Archive is the first volume to bring together a range of methodological approaches to the materiality of archives, as a framework for their engagement, analysis and interpretation. Focusing on the archives of creative practices, the book reaches between and across existing bodies of knowledge in this field, including material culture, art history and literary studies, unified by an interest in archives as material deposits and aggregations, in both analogue and digital forms, as well as the material encounter. Connecting a breadth of disciplinary interests in the archive with expanding discourses in materiality, contributors address the potential of a material engagement to animate archival content. Analysing the systems, processes and actions that constitute the shapes, forms and structures in which individual archival objects accumulate, and the underpinnings which may hold them in place as an archival body, the book considers ways in which the inexorable move to the digital affects traditional theories of the physical archival object. It also considers how stewardship practices such as description and metadata creation can accommodate these changes. The Materiality of the Archive unifies theory and practice and brings together professional and academic perspectives. The book is essential reading for academics, researchers and postgraduate students working in the fields of archive studies, museology, art history and material culture.